1994
DOI: 10.1139/m94-102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon and nitrogen metabolism on nitrate reductase activity of Rhodobacter capsulatus E1F1

Abstract: The phototrophic bacterium Rhodobacter capsulatus E1F1 possesses an assimilatory, inducible nitrate reductase that is regulated by carbon and nitrogen metabolism. Nitrate reductase activity was detected in cells cultured with amino acids and nitrate as simultaneous nitrogen source but it required an additional carbon source such as D,L-malate. A significant rise in nitrate reductase activity was observed in media with increasing nitrate concentrations up to 10 mM KNO3, although higher nitrate concentrations ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 16 publications
3
12
0
Order By: Relevance
“…In addition, ammonium has no effect on nap gene expression ( Table 2, Fig. 6), confirming previous observations (10,28).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In addition, ammonium has no effect on nap gene expression ( Table 2, Fig. 6), confirming previous observations (10,28).…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, the in vitro Nap activity assayed with reduced MV as an artificial electron donor is a measure of the total activity, independent of NapC and the redox state of the quinol pool, even when the Nap system is not being used by the cells due to the absence of an electron supply. In earlier studies, it was observed that MV-Nap activity in R. sphaeroides is higher under heterotrophic aerobic than under phototrophic anaerobic conditions and that the activity is stimulated by nitrate but unaffected by ammonium or the C/N balance (10,28). However, a detailed study on the regulation of Nap activity or nap gene expression under different conditions has not been performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, nitrite accumulation did not match nitrate consumption, indicating that, as observed previously (Sears et al, 1997) have been undertaken in Rhodobacter sp. and Escherichia coli (Darwin et al, 1998;Dobao et al, 1994;Gavira et al, 2002;Liu et al, 1999;Reyes et al, 1998;Stewart et al, 2002;Wang et al, 1999). A notable feature of Nap systems is the variation, both within and between organisms, in the physiological functions, as well as the regulation and expression, of nap.…”
Section: Discussionmentioning
confidence: 99%
“…The Nap system of R. sphaeroides DSM158 is encoded by the napKEFDABC gene cluster, and the regulation of the system has been studied Reyes et al, 1996Reyes et al, , 1998. In vivo Nap activity is not responsive to the intracellular C/N ratio (Dobao et al, 1994), but is regulated by enzyme activation in response to the carbon substrate/electron supply and nitrate concentration (Gavira et al, 2002). Interestingly, in response to nitrate under anaerobic photoheterotrophic conditions with an oxidized carbon substrate, enzyme activation causes increased in vivo Nap activity (Gavira et al, 2002) (see below).…”
Section: Introductionmentioning
confidence: 99%